Penerapan Pakan Mandiri dan Budidaya Ikan Nila Sistem Bioflok bagi Kelompok Pembudidaya Ikan di Kelurahan Kaisabu Baru Kota Baubau Provinsi Sulawesi Tenggara: Implementation of Self-Produced Feed and Tilapia Culture Based on the Biofloc System for the Fish Farmers Group in Kaisabu Baru Village, Baubau City, Southeast Sulawesi Province - Sumitro, Sumitro; Afandi, Arfan; Estiani, Estiani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Bangkali Fish Farmers Group (POKDAKAN) is one of the groups supported by the Fisheries Department of Baubau City in Kaisabu Baru Village, whose business has struggled to grow due to the high cost of commercial feed and the continued use of conventional farming methods. The solution is to implement self-produced feed and tilapia farming based on the biofloc system. This community service activity aims to provide knowledge to the Bangkali Fish Farmers Group about producing self-made feed and implementing tilapia farming based on the biofloc system. The methods used in this community service activity include program socialization, the implementation of self-produced feed, and the farming of tilapia using the biofloc system. The result of this activity is that the Bangkali group is now capable of producing their feed and able to apply the tilapia culture based on the biofloc system.